2007
DOI: 10.1177/1077800407304413
|View full text |Cite
|
Sign up to set email alerts
|

Jarheads, Girly Men, and the Pleasures of Violence

Abstract: This article explores the troublesome ways in which violence and pleasure become conflated for both hypermasculine and effeminate men. Using images from contemporary culture and incidents from the author's life, the article ponders how men might negotiate this unfortunate bind. I n the film, Jarhead, a group of Marines gang up on another member of their platoon. Held down, the targeted man is threatened with a branding, with burning into his skin the insignia of the Marines. We see his resistance, his fear, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 6 publications
0
13
0
3
Order By: Relevance
“…This is significant as Zebrack (2000) has suggested that these changes in identity narratives have clinical and psychosocial implications, affecting one’s ability to carry out roles and responsibilities, and, depending on the context, negatively affect overall QoL. As gender figures heavily in narrative and identity construction (Pelias, 2007, 2008), exploring the physical (e.g., hair loss) and psychosocial (e.g., feminine roles) reported aspects that contribute to constructions of the self through a gendered lens may be useful in promoting well-being after cancer. Interestingly, the studies exploring men’s experience with understanding gender focused largely on physical challenges (e.g., physical capacity, work; Morrison & Thomas, 2015; Oliffe & Bottorff, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This is significant as Zebrack (2000) has suggested that these changes in identity narratives have clinical and psychosocial implications, affecting one’s ability to carry out roles and responsibilities, and, depending on the context, negatively affect overall QoL. As gender figures heavily in narrative and identity construction (Pelias, 2007, 2008), exploring the physical (e.g., hair loss) and psychosocial (e.g., feminine roles) reported aspects that contribute to constructions of the self through a gendered lens may be useful in promoting well-being after cancer. Interestingly, the studies exploring men’s experience with understanding gender focused largely on physical challenges (e.g., physical capacity, work; Morrison & Thomas, 2015; Oliffe & Bottorff, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…By navigating truthfulness about biases, transparency with our vulnerabilities, and connectedness to the human experience, we sought to tell a story on ourselves (Allen & Piercy, 2005), offering glimpses of our local knowledge and ourselves in connection to others (Pelias, 2007). Our discussions and writings highlighted the multifaceted nature of the construction of MFT professional identity mandating participation in social justice advocacy and multidisciplinary collaboration.…”
Section: Resultsmentioning
confidence: 98%
“…An autoethnographer uses personal experience to make unique and unfamiliar aspects of a group familiar for insiders and outsiders, and, in so doing, say something about or motivate change in a particular culture(s) (e.g., Bochner 2002; Boylorn 2006; Ellis 2002, 2009; Pelias 2004, 2007). An autoethnographer may also interview cultural members (e.g., Ellis, Kiesinger, and Tillmann‐Healy 1997; Foster 2006; Marvasti 2006) and analyze cultural artifacts (e.g., Boylorn 2008; Denzin 2006), but does not apply predetermined, sense‐making criteria to her, his, or others' experience and the artifacts; rather, the person allows patterns to emerge, inductively, through analysis of the experience and artifacts.…”
Section: Autoethnography: Methods and Datamentioning
confidence: 99%